Coagulated Mineral Adsorbents for Dye Removal, and Their Process Intensification Using an Agitated Tubular Reactor (ATR) - Alastair S. Tonge; David Harbottle; Simon Casarin; Monika Zervaki; Christel Careme; Timothy N. Hunter (ChemEngineering, 2021)
The aim of this study was to understand the efficacy of widely available minerals as dual-function adsorbers and weighter materials, for the removal of toxic azo-type textile dyes when combined with coprecipitation processes. Specifically, the adsorption of an anionic direct dye was measured on various mineral types with and without the secondary coagulation of iron hydroxide (‘FeOOH’) in both a bench-scale stirred tank, as well as an innovative agitated tubular reactor (ATR). Talc, calcite and modified bentonite were all able to remove 90–95% of the dye at 100 and 200 ppm concentrations, where the kinetics were fitted to a pseudo second-order rate model and adsorption was rapid (<30 min). Physical characterisation of the composite mineral-FeOOH sludges was also completed through particle size and sedimentation measurements, as well as elemental scanning electron microscopy to determine the homogeneity of the minerals in the coagulated structure. Removal of >99% of the dye was achieved for all the coagulated systems, where additionally, they produced significantly enhanced settling rates and bed compression. The greatest settling rate (9 mm min−1) and solids content increase (450% w/w) were observed for the calcium carbonate system, which also displayed the most homogenous distribution. This system was selected for scale-up and benchmarking in the ATR. Dye removal and sediment dispersion in the ATR were enhanced with respect to the bench scale tests, although lower settling rates were observed due to the relatively high shear rate of the agitator. Overall, results highlight the applicability of these cost-effective minerals as both dye adsorbers and sludge separation modifiers to accelerate settling and compression in textile water treatment. Additionally, the work indicates the suitability of the ATR as a flexible, modular alternative to traditional stirred tank reactors.